Paracetamol overdose associated with cortical blindness-complicated acute leukoencephalopathy: a case report - Ruba Khasawneh; Nour Keewan; Samah K. Aburahma; Basel Waleed Khurfan (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Paracetamol is one of the most used antipyretics and analgesics among pediatrics, and its overdose is highly encountered among pediatrics especially in the pre-school age. While it is well-known that paracetamol overdose may lead to toxicities including severe hepatic toxicity, some recent reports have highlighted its “in situ” toxicity on brain tissue at high doses, even in the absence of hepatotoxicity. This can result in acute leukoencephalopathy (AL), coma, or even death. This report describes a case of a child who developed cortical blindness-complicated AL, following a paracetamol overdose. Case presentation An 18-month-old previously healthy girl accidentally ingested 300 mg/kg of paracetamol suspension. After ingestion, the child was in an initial bad condition that has gradually improved. Several days after ingestion, the patient lost her vision, and she remained blind since then despite a newer appreciation to light. The initial brain magnetic resonance imaging (MRI) suggested AL demonstrated as a faint high T2/fluid-attenuated inversion recovery (FLAIR) signal intensity in the cortical and subcortical regions of both parieto-occipital lobes with sulcal effacement and restricted diffusion. After around 3 months, the subsequent brain MRI showed involutional changes that were manifested as a brain volume loss in the same areas with evidence of gyri-form laminar necrosis in both parieto-occipital regions without restricted diffusion. Other brain MRI findings include right cerebral convexity hyperacute subdural hematoma with prominent subarachnoid spaces. Conclusions The child developed cortical blindness-complicated AL following a paracetamol overdose. It is well- known that AL may result from several toxins by their direct and/or indirect effect on the cerebral white matter. However, there is still no enough data in the literature clearly explaining the relation of paracetamol overdose to AL. The generally proposed effect of paracetamol on the brain is mainly justified by the excessive oxidative stress. Further studies at the cellular and genetic levels are still needed to investigate the exact association between paracetamol overdose and AL, as well as the underlying mechanisms involved.